2012 IEEE 10th Symposium on Embedded Systems for Real-Time Multimedia 2012
DOI: 10.1109/estimedia.2012.6507023
|View full text |Cite
|
Sign up to set email alerts
|

Memory-centric VDF graph transformations for practical FPGA implementation

Abstract: Realising memory intensive applications such as image and video processing on FPGA requires creation of complex, multi-level memory hierarchies to achieve real-time performance; however commerical High Level Synthesis tools are unable to automatically derive such structures and hence are unable to meet the demanding bandwidth and capacity constraints of these applications. Current approaches to solving this problem can only derive either single-level memory structures or very deep, highly inefficient hierarchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This paper presents an approach to overcoming this limitation. By extending foundation work in [5][6] a constructive [7] approach is presented which derives FPGA RTL accelerators, including all requisite on-chip and off-chip memory storage, from a C kernel specification to meet a user-defined throughput requirement. To the best of the authors' knowledge this is the first reported approach to achieve this capability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This paper presents an approach to overcoming this limitation. By extending foundation work in [5][6] a constructive [7] approach is presented which derives FPGA RTL accelerators, including all requisite on-chip and off-chip memory storage, from a C kernel specification to meet a user-defined throughput requirement. To the best of the authors' knowledge this is the first reported approach to achieve this capability.…”
mentioning
confidence: 99%
“…Employing streaming interfaces5 Note that, for consistency, no manual manipulation or annotation of input source, nor manual direction, is given to any of the tools compared in this sectionApril 26, 2016 DRAFT…”
mentioning
confidence: 99%